APLIKASI SISTEM PAKAR UNTUK IDENTIFIKASI VIRUS COVID 19 MENGGUNAKAN METODE CERTAINTY FACTOR BERBASIS FRAMEWORK LARAVEL - Aris Munandar Harahap; Yusra Fadhillah (Jurnal Education and Development, 2023)
Coronavirus is a collection of viruses that can infect the respiratory system. In most cases, this virus causes only mild respiratory infections, such as the flu. However, this virus can also cause severe respiratory infections such as lung infections (pneumonia). An expert system is a computer-based system that uses knowledge, facts and reasoning techniques in solving a problem that can usually only be solved by someone who is an expert in their field. The purpose of this research is to design and build an application or software expert system based on the Laravel framework that is able to identify coronavirus (covid). This study uses the method of analyzing the value of certainty certainty factor, based on answers to questions given by the user. The results displayed are the condition of the user connected to covid, the results are also equipped with an explanation of covid which is displayed in the form of a website using the Laravel framework. The conclusion in this study is that the Laravel framework is proven to be able to be implemented in engineering expert systems for covid identification. The certainty factor method is proven to be able to optimally search or track the symptoms of the covid virus by providing a certainty value. The online system can help users get information about the types of covid virus, symptoms and types of referrals or handling of the covid virus.